IMPLEMENTASI TEKNOLOGI DALAM PENGUATAN LITERASI DAN NUMERASI SEBAGAI STRATEGI PENINGKATAN PRODUKTIVITAS SUMBER DAYA MANUSIA JANGKA PANJANG (STUDI KASUS SDN 3 PASAMAN) - Dianti, Muthia Rahma; Mustafa, Lula (Smart Education, 2026)
Abstract: Technology implementation plays a strategic role in improving the quality of human resources as a fundamental foundation of long-term economic productivity. From a human capital economics perspective, basic education represents the initial phase of human capital formation that determines individuals’ future productive capacity. This study aims to analyze the implementation of technology in strengthening literacy and numeracy as a human capital formation strategy from the elementary education level to promote long-term productivity gains. This research employs a descriptive qualitative approach with a case study design conducted at SDN 3 Pasaman, focusing on fourth- and fifth-grade students. Data collection techniques include observations of technology-based learning, documentation of school programs, and analysis of students’ literacy and numeracy achievements as early indicators of human resource quality. The results indicate that the structured use of educational technology enhances the effectiveness of literacy and numeracy strengthening as foundational competencies for digital human resources. The improvement of these competencies has the potential to generate productivity gains through increased cognitive capacity, adaptability, and future workforce readiness. This study confirms that integrating technology with literacy and numeracy strengthening constitutes an economically relevant strategy for digital human resource development and the enhancement of national economic competitiveness. Keywords: Technology Implementation, Literacy, Numeracy, Digital Human Capital, Human Resource Productivity Abstrak: Implementasi teknologi memiliki peran strategis dalam meningkatkan kualitas sumber daya manusia sebagai fondasi utama produktivitas ekonomi jangka panjang. Dalam perspektif ekonomi sumber daya manusia, pendidikan dasar merupakan fase awal pembentukan human capital yang menentukan kapasitas produktif individu di masa depan. Penelitian ini bertujuan untuk menganalisis implementasi teknologi dalam penguatan literasi dan numerasi sebagai strategi human capital formation sejak jenjang pendidikan dasar guna mendorong productivity gain jangka panjang. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan desain studi kasus di SDN 3 Pasaman yang berfokus pada siswa kelas IV dan V. Teknik pengumpulan data dilakukan melalui observasi pembelajaran berbasis teknologi, dokumentasi program sekolah, serta analisis capaian literasi dan numerasi siswa sebagai indikator awal kualitas sumber daya manusia. Hasil penelitian menunjukkan bahwa pemanfaatan teknologi pembelajaran secara terstruktur meningkatkan efektivitas penguatan literasi dan numerasi sebagai kompetensi dasar pembentuk sumber daya manusia digital. Peningkatan kompetensi tersebut berpotensi menghasilkan productivity gain melalui peningkatan kapasitas kognitif, adaptabilitas, dan kesiapan tenaga kerja di masa depan. Penelitian ini menegaskan bahwa integrasi teknologi dengan penguatan literasi dan numerasi merupakan strategi ekonomi yang relevan dalam pembangunan sumber daya manusia digital dan peningkatan daya saing ekonomi nasional. Kata Kunci : Implementasi Teknologi, Literasi, Numerasi, Sumber Daya Manusia Digital, Produktivitas Sumber Daya Manusia